Non-Convulsive Status Epilepticus (NCSE) in ICU - Wiryana, Made; Sinardja, I Ketut; Aryabiantara, I Wayan; GdeAgung Senapathi, Tjokorda; Gede Widnyana, I Made; Utara Hartawan, I Gusti Agung Gede; Parami, Pontisomaya; Ryalino, Christopher; Putra Pradhana, Adinda (Bali Journal of Anesthesiology, 2017)
Epilepsy is a neurological disorder characterized by recurrent epileptic seizures. Non-convulsive status epilepticus (NCSE) is defined as a persistent change in mental status as opposed to the previous conditions, lasted at least 30 minutes long,Â  associated with continuous spike wave epileptiform EEG changes. Clinical manifestation of NCSE can present as confusion, personality changes, psychosis, and coma. Indeed NCSE prognosis is dependent on the underlying etiology of persistent EEG changes of. Preferred medication is focus on improving its fundamental pathological changes, such as metabolic disorders, infection, drugs toxicity, and immediate pharmacological treatment. Intravenous benzodiazepine is recommended asthe first drug of choice for NCSE and early recognition of treatment response can help to establish the diagnosis.Â  This patient has a good outcome which was influenced with short ictal period from the first episode upon arrival on reffered hospital, good initial response and management on emergency department, a conduct and thorough ICU monitoring, as well as the effective treatment response.